Analysis of the CC chemokine receptor 5Delta32 polymorphism in pediatric liver transplant recipients - Fischer-Maas, Louise; Schneppenheim, Reinhard; Oyen, Florian; Grabhorn, Enke; Richter, Andrea; Fischer, Lutz; Ganschow, Rainer (Pediatric transplantation, 2008)
In adult liver graft recipients, it has been shown that certain chemokine polymorphisms (CCR5Delta32) may correspond to ischemic type biliary lesions leading to chronic graft dysfunction. The aim of our present study was to assess the importance of CCR5Delta32 polymorphism in a cohort of pediatric liver graft recipients with regard to acute or chronic graft dysfunction. A total of 137 children post-liver transplantation have been included for genetic analysis (CCR5Delta32 polymorphism), and the incidence of acute and chronic graft dysfunction was analyzed. The most common diagnosis leading to LTx was biliary atresia (56.2%), the median age was 14 months, and 33.5% of the patients received a living-related graft. In all, 110 of the subjects were found to have the CCR5 wild type, 25 children were heterozygous for CCR5Delta32, and two patients were homozygous. Of 137, 44 (32.1%) developed acute graft rejection, nine out of 137 (6.6%) chronic graft dysfunction (vanishing bile duct syndrome), and 84 (61.3%) children had neither acute nor chronic graft rejection. There was no significant correlation between acute graft rejection or chronic graft dysfunction and the CCR5Delta32 allele in the study population. We conclude that CCR5Delta32 polymorphism may not play a role in acute or chronic liver graft dysfunction in children.